Análise arquitetural de algoritmos criptográficos assimétricos em plataformas embarcadas usadas em RSSF - Quirino, Gustavo da Silva (2013)
This work consists in a performance evaluating of Asymmetrical cryptographic algorithms in embedded platforms used in Wireless Sensor Networks (WSN). The sensor devices have low computing power and energy, therefore safety techniques should not consume large amounts of resources. The asymmetric cryptographic algorithms RSA, ECC and MQQ were evaluated on platforms Desktop, ARM, MSP430 and AVR. The evaluations were performed using the SimpleScalar simulators, Sim-Panalyzer, MSPsim and AVRORA . The evaluation criteria were: processing time, memory usage and processor, as well as energy consumption. The data showed that the algorithm MQQ was more efficient than RSA and ECC algorithms in most assessment criteria, in addition, the ECC algorithm obtained the best results when compared with the RSA algorithm